Calculation of microwave plasma oscillations in high temperaturesuperconductors - (:unkn) unknown (SPRINGER, 2007)
It has been determined that the superconducting system, that consists of copper oxide based mercury oxide, behaves as if an oscillating cavity with the plasma frequency of 10(12) Hz under particular amount of magnetic field at space temperature of 100 K. Moreover, plasma frequency of superconducting system (mercury based superconductors) were found to be varying from infrared to microwave region by increasing the temperature from liquid helium of 4.2 K to space temperature of about 100 K. Furthermore, by dealing with calculations of Lawrance-Doniach Model it was found that the plasma frequency versus temperature relation satisfies the sigmoidal distribution whereas the anisotropy factor coincides with the polynomial fitting function.
Keywords: resonance; microwave plasma oscillation; 3-D Bose-Einstein condensation; C-AXIS; T-C; TEMPERATURE; SUPERCONDUCTORS